Bruton's Tyrosine Kinase Links the B Cell Receptor to Nuclear Factor κb Activation - Bajpai, Urmila D. (The Rockefeller University Press, 2000)
The recognition of antigen by membrane immunoglobulin M (mIgM) results in a complex series of signaling events in the cytoplasm leading to gene activation. Bruton's tyrosine kinase (BTK), a member of the Tec family of tyrosine kinases, is essential for the full repertoire of IgM signals to be transduced. We examined the ability of BTK to regulate the nuclear factor (NF)-κB/Rel family of transcription factors, as the activation of these factors is required for a B cell response to mIgM. We found greatly diminished IgM- but not CD40-mediated NF-κB/Rel nuclear translocation and DNA binding in B cells from X-linked immunodeficient (xid) mice that harbor an R28C mutation in btk, a mutation that produces a functionally inactive kinase. The defect was due, in part, to a failure to fully degrade the inhibitory protein of NF-κB, IκBα. Using a BTK-deficient variant of DT40 chicken B cells, we found that expression of wild-type or gain-of-function mutant BTK, but not the R28C mutant, reconstituted NF-κB activity. Thus, BTK is essential for activation of NF-κB via the B cell receptor.